2015
DOI: 10.1021/jacs.5b02069
|View full text |Cite
|
Sign up to set email alerts
|

A Reversible and Highly Selective Inhibitor of the Proteasomal Ubiquitin Receptor Rpn13 Is Toxic to Multiple Myeloma Cells

Abstract: The proteasome is a multi-subunit complex responsible for most non-lysosomal turnover of proteins in eukaryotic cells. Proteasome inhibitors are of great interest clinically, particularly for the treatment of multiple myeloma (MM). Unfortunately, resistance arises almost inevitably to these active site-targeted drugs. One strategy to overcome this resistance is to inhibit other steps in the protein turnover cascade mediated by the proteasome. Previously, Anchoori et al. identified Rpn13 as the target of an ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
92
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(93 citation statements)
references
References 49 publications
1
92
0
Order By: Relevance
“…Two independently discovered hRpn13-targeting molecules are reported to restrict multiple myeloma cells (9,10). We have found that one such molecule, RA190, interferes with DNA replication and G 2 progression in HeLa cells (Fig.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Two independently discovered hRpn13-targeting molecules are reported to restrict multiple myeloma cells (9,10). We have found that one such molecule, RA190, interferes with DNA replication and G 2 progression in HeLa cells (Fig.…”
Section: Discussionmentioning
confidence: 93%
“…We recently discovered a bisbenzylidine piperidone class of molecules that restricts mouse xenograft models of multiple myeloma and ovarian cancer and covalently attaches to the proteasome ubiquitin receptor hRpn13 (9). Another group independently also identified an hRpn13-targeting molecule to restrict multiple myeloma cells (10).…”
mentioning
confidence: 99%
“…In HCT116 cells, RA190 can also bind with UCH37, a deubiquitinating enzyme interacting with ADRM1, to suppress proteasome function [35]. Meanwhile, it was reported that KDT-11 could also suppress multiple myeloma by targeting ADRM1 [36]. In ICC cells the specificity of RA190 on ADRM1 inhibition was confirmed by : (1) the accumulation of higher-molecular weight polyubiquitylated proteins and p-IκBα in RA190-treated ICC cells; and (2) reduced RA190 sensitivity following knockdown of ADRM1 in ICC cells [14].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the human Rpn13/ADRM1 gene is overexpressed in lung, ovarian, colon, liver, kidney, bladder, and stomach cancers (18), and ADRM1 amplification in ovarian cancers correlates significantly with shorter time to recurrence and death (19). The Rpn13/ADRM1 inhibitor RA190 inhibits proteasome functions, triggers apoptosis, and restricts cancer growth in mice xenografts (20), and similar effects were observed with an Rpn13/ADRM1-targeting peptoid inhibitor (21). hHR23B has been identified as a candidate cancer biomarker that governs the response and sensitivity of tumor cells to HDAC inhibitors (22,23).…”
mentioning
confidence: 89%